Fixed Point of Suzuki-Geraghty Type 𝜃-Contractions in Partial Metric Spaces with Some Applications - Wudthichai Onsod; Poom Kumam; Teerapol Saleewong (Science & Technology Asia, 2023)
The aim of this paper is to introduce the notions of Suzuki-Geraghty type 𝜃- contractions and to establish some fixed point theorems in the setting of complete partial metric spaces and give an example to illustrate these main results. Moreover, we utilize our results to study the existence problem of solutions of nonlinear Hammerstein integral equations.